Economic instability and its effect on brand preferences: big data examination of self-image and online shopping conduct - Johnson, Nuraeni Saripudin; Purwanegara, Mustika Sufiati; Mulyono, Nur Budi (Business, Management and Economics Engineering, 2026)
Purpose – This study will examine how consumer brand preference is impacted by economic instability in the market of e-commerce in Indonesia, the relationship between self-image and purchasing patterns under three different periods; pre-crisis (2017–2019), crisis (2020–2022), and post-crisis recovery (2022–2023).Research methodology – Transactional variables (Total payment volume, average order value, and purchase frequency) were analyzed using the mixed-methods approach in three brand categories (global, local, unbranded) and two product subcategories (care, decorated). ANO- VA and T-tests were used as a quantitative analysis of one of the largest Indonesian e-commerce platforms. The methods of qualitative analysis included semi-structured interviews with 20 industry experts who were chosen while engaging in purposive sampling and analyzed based on thematic analysis, in order to understand the emergent themes and patterns.Findings – The findings indicate that the preference of global brands declined throughout the period of crisis (Z-sales declined 1.84 to –0.002) whereas local brands rejuvenated through community-oriented messages. The balanced status and sense of practicality seen in the post-crisis consumption saw global brands partially recovering (Z-sales: 1.43) and status-related self-image shifted into the health-conscious and community-supportive groups.Research limitations – The study has a limitation of studying the e-commerce market and beauty product of Indonesia and the generalization to other regions or products. Besides, the qualitative element is based on only 14 internal experts working in the e-commerce and beauty sectors, which is insufficient to reflect direct consumer experiences and motivation to behaviour. Although the managerial interpretations bring about strategic data, the findings on self-image and consumer psychology should be confirmed by conducting empirical research with customers.Practical implications – The results illustrate the significance of matching message of the brand with changing consumer values and using big data to create personalized marketing plans.Originality/Value – This study is the first one to synthesize big data analysis with the use of expertise to indicate how consumer self-perception and purchase behavior are redefined due to economic shocks in online markets.